Regulation of glucose and glycogen metabolism during and after exercise - Jensen, T. E.; Richter, E. A. (The Journal of Physiology, 2012)
Utilization of carbohydrate in the form of intramuscular glycogen stores and glucose delivered from plasma becomes an increasingly important energy substrate to the working muscle with increasing exercise intensity. This review gives an update on the molecular signals by which glucose transport is increased in the contracting muscle followed by a discussion of glycogen mobilization and synthesis by the action of glycogen phosphorylase and glycogen synthase, respectively. Finally, this review deals with the signalling relaying the well-described increased sensitivity of glucose transport to insulin in the post-exercise period which can result in an overshoot of intramuscular glycogen resynthesis post exercise (glycogen supercompensation).